Maternal dietary fatty acid composition and newborn epigenetic aging—a geometric framework approach. Issue 1 (27th October 2021) - Koemel, Nicholas A; Senior, Alistair M; Dissanayake, Hasthi U; Ross, Jason; McMullan, Rowena L; Kong, Yang; Phang, Melinda; Hyett, Jon; Raubenheimer, David; Gordon, Adrienne; Simpson, Stephen J; Skilton, Michael R
ABSTRACT: Background: Maternal nutrition is associated with epigenetic and cardiometabolic risk factors in offspring. Research in humans has primarily focused on assessing the impact of individual nutrients. Objectives: We sought to assess the collective impact of maternal dietary MUFAs, PUFAs, and SFAs on epigenetic aging and cardiometabolic risk markers in healthy newborn infants using a geometric framework approach. Methods: Body fatness ( n  = 162), aortic intima–media thickness (aIMT; n  = 131), heart rate variability ( n  = 118), and epigenetic age acceleration ( n  = 124) were assessed in newborn infants. Maternal dietary intake was cross-sectionally assessed in the immediate postpartum period via a validated 80-item self-administered FFQ. Generalized additive models were used to explore interactive associations of nutrient intake, with results visualized as response surfaces. Results: After adjustment for total energy intake, maternal age, gestational age, and sex there was a 3-way interactive association of MUFAs, PUFAs, and SFAs ( P  = 0.001) with newborn epigenetic aging. This suggests that the nature of each fat class association depends upon one another. Response surfaces revealed MUFAs were positively associated with newborn epigenetic age acceleration only at proportionately lower intakes of SFAs or PUFAs. We also demonstrate a potential beneficial association of omega-3 (n–3) PUFAs with newborn epigenetic age acceleration ( P  = 0.008). There was no significant association of fat class with newborn aIMT, heart rate variability, or body fatness. Conclusions: In this study, we demonstrated an association between maternal dietary fat class composition and epigenetic aging in newborns. Future research should consider other characteristics such as the source of maternal dietary fatty acids.